Antibacterial, antitussive, antioxidant and toxicological evaluation of Joshanda lozenges - Monika Bansala, Monica Gulatib, Sachin Kumar Singhb, Sanjiv Duggalc (Journal of Applied Pharmaceutical Science, 2015)
Joshanda, a Greco-urban formulation comprising seven herbs has been used since centuries for the treatment of cold, cough and associated allergic reactions. Conventionally, it is used in the form of an extemporaneously prepared decoction. However, in the current scenario, lozenges happen to be the dosage form of choice for antitussive drugs. In case of polyherbal drugs, the dosage form assumes a great importance in order to ensure that all the phyto-components exert their pharmacological effect to the maximum. Based on the popularity of lozenges, conventional decoction form of Joshanda was formulated in the form of lozenges. Lozenges were evaluated for routine quality control tests. The most remarkable feature of the formulation was that excellent compression, hardness, friability and disintegration properties could be achieved without the addition of any external binder. The prepared formulation was subjected to in vitro antioxidant activity, antibacterial activity against common respiratory tract pathogens, in vivo antitussive activity and acute toxicity studies using Albino Wistar mice. Accelerated stability studies were conducted as per ICH guidelines. The performance of lozenges was found to be satisfactory in all the tested aspects. Our study proposes the use of lozenges as a preferred dosage form of the conventionally used decoction of Joshanda.
Keywords: Joshanda,Lozenges, Antitussive, Antibacterial, Stability Studies, Acute Toxicity.